Development and verification of a new nuclear data processing code AXSP - Hu, Kui; Ma, Xubo; Ma, Xuan; Huang, Yuqin; Zhang, Chen; Chen, Yixue (Frontiers in Energy Research, 2022)
Advanced reactor design needs more accurate cross section generation code. In this study, a new nuclear data processing code named AXSP is developed and the method and performance of which are described. Compared with the NJOY program, the precision of the unresolved resonance processing module has been significantly improved due to the adoption of a more accurate solution method and an optimized sorting algorithm, at the same time, other modules of AXSP are relatively comprehensive. At present, the function of resolved resonance cross section reconstruction and linearization is ReconXS module. Doppler broadening module is BroadXS by using Gauss-Hermite quadrature and Gauss-Legendre quadrature from 0 K temperature pointwise cross section to any temperature which is defined by the user. The shielding factor in the unresolved resonance energy region is calculated by the UnresXS or the PUnresXS module, which are developed based on the Bondarenko method and the probability table method respectively. The ACE formatted cross sections for Monte Carlo code is processing by ACEXS module, and the multi-group cross sections are generated by GroupXS module. The cross sections processed by different module were verified by the NJOY2016 code, and the multigroup cross sections were also verified by using the critical benchmarks. the multiplication factor difference between AXSP and NJOY2016 are less than 20 pcm. Besides this, the ZPR6/7 fast reactor is used for ACE format library verification. The results show that the criticality calculated by AXSP have a good agreement with that of NJOY2016.